Implementing reversed-phase and hydrophilic interaction liquid chromatography into the characterization of DTPA-ramucirumab conjugate before radiolabeling - Naplekov, Denis K; Bárta, Pavel; Trejtnar, František; Sklenářová, Hana; Lenčo, Juraj (Journal of pharmaceutical and biomedical analysis, 2023)
Radioimmunoconjugates represent a promising class of therapeutics and diagnostics. The characterization of intermediate chelator-antibody products, i.e., without the radionuclide, is frequently omitted, bringing significant uncertainty in the radioimmunoconjugate preparation. In the present study, we explored the utility of reversed-phase (RPLC) and hydrophilic interaction (HILIC) liquid chromatography with UV detection to characterize ramucirumab stochastically conjugated with p-SCN-Bn-CHX-A"-DTPA chelator (shortly DTPA). The conjugation was well reflected in RPLC chromatograms, while chromatograms from HILIC were significantly less informative. RPLC analyses at the intact level confirmed that the conjugation resulted in a heterogeneous mixture of modified ramucirumab. Moreover, the RPLC of DTPA-ramucirumab confirmed heterogeneous conjugation of all subunits. The peptide mapping did not reveal substantial changes after the conjugation, indicating that most parts of ramucirumab molecules remained unmodified and that the DTPA chelator was bound to various sites. Eventually, the RPLC method for analysis of intact ramucirumab was successfully applied to online monitoring of conjugation reaction in 1 h intervals for a total of 24 h synthesis, which readily reflected the structural changes of ramucirumab in the form of retention time shift by 0.21 min and increase in peak width by 0.22 min. The results were obtained in real-time, practically under 10 min per monitoring cycle. To the best of our knowledge, our study represents the first evaluation of RPLC and HILIC to assess the quality of intermediates during the on-site preparation of radioimmunoconjugates prior to radiolabeling.
Keywords: hydrofobní a hydrofilní interakce; Immunoconjugates; chromatografie s reverzní fází; Hydrophobic and Hydrophilic Interactions; Chelating Agents; Chromatography, Reverse-Phase; chelátory; Pentetic Acid; imunokonjugáty; kyselina pentetová; Chromatography, Liquid; chromatografie kapalinová